Residents’ perception of tourism impacts and attitude toward tourism development: A socio-cultural perspective analysis in jaffna district - Hamzayini, P.; Arachchige, R.S.S.W. (University of Jaffna, 2020)
Residents’ attitude/support towards tourism development has engrossed many scholars' attention in tourism studies. To give the importance of understanding the residents’ attitude towards tourism development and understand the limitations in understanding the perception of residents based on socio-cultural factors, this study endeavored to model the residents’ s support for tourism development based on the study of socio cultural impacts. To identify the relationship with dependent and independent variables, several hypotheses were developed and were tested to achieve the major objectives of this study such as identifying the most significant determinants of the perceived impacts of tourism development, assessing how the determining factors affect the perceived impacts of tourism development and determining how the perceived impacts affect the attitude towards tourism development. The proposed socio-cultural research framework has predicted the impact of knowledge about tourism, intrinsic motivation factors, community attachment, and community concern on residents’ support for tourism development in Jaffna district through the mediating variables of perceived socio cultural benefits and perceived socio-cultural costs. The perceptions of 600 residents were collected through a stratified random sampling technique. The model and hypothesis paths were tested using Structural Equation Modeling with the aid of AMOS and SPSS software packages. Findings disclose that residents’ support for tourism development in Jaffna district is a role of perceived socio-cultural benefits and costs perceived by residents and four independent variables of knowledge about tourism, intrinsic motivation factors, community attachment, and community concern. The results reveal that the perception regarding tourism impacts might create both positive and negative attitudes regarding tourism development in Jaffna district, which might assist in gaining support from the residents regarding tourism development.
Keywords: Perceived impacts; Residents’ support for tourism development and socio-cultural impacts